Relativistic jets shine through shocks or magnetic reconnection? - Sironi, Lorenzo; Petropoulou, Maria; Giannios, Dimitrios (OUP, 2015)
Observations of gamma-ray-bursts and jets from active galactic nuclei reveal that the jet flow is characterized by a high radiative efficiency and that the dissipative mechanism must be a powerful accelerator of non-thermal particles. Shocks and magnetic reconnection have long been considered as possible candidates for powering the jet emission. Recent progress via fully-kinetic particle-in-cell simulations allows us to revisit this issue on firm physical grounds. We show that shock models are unlikely to account for the jet emission. In fact, when shocks are efficient at dissipating energy, they typically do not accelerate particles far beyond the thermal energy, and vice versa. In contrast, we show that magnetic reconnection can deposit more than 50 per cent of the dissipated energy into non-thermal leptons as long as the energy density of the magnetic field in the bulk flow is larger than the rest-mass energy density. The emitting region, i.e. the reconnection downstream, is characterized by a rough energy equipartition between magnetic fields and radiating particles, which naturally accounts for a commonly observed property of blazar jets.
Keywords: acceleration of particles; Astrophysics - High Energy Astrophysical Phenomena; galaxies: jets; gamma-ray burst: general; magnetic reconnection; radiation mechanisms: non-thermal; shock waves